Fate of 210Pbex fallout in soil under forest and scrub of the central Spanish Pre‐Pyrenees. (May 2017) - Gaspar, L.; Webster, R.; Navas, A.
Summary: The characteristics and distribution of unsupported radioactive lead‐210 ( 210 Pbex ) in soil and the relations between the radionuclide and soil properties determine its fate within the environment. We have explored the distribution of 210 Pbex in stony soil profiles near the edge of the Ebro basin in northern Spain, the role played by vegetation in that distribution, and the relation between the radionuclide and organic carbon. We describe in detail the profiles of 210 Pbex at 23 sites, 10 under forest and 13 under scrub, which were sampled at 2‐cm intervals to a maximum depth of 14 cm. The theoretical distribution of 210 Pbex follows an exponential decline with depth in undisturbed soil, assuming minimal surface slope and no evidence of erosion or deposition processes. Comparable distribution patterns of 210 Pbex and organic C became evident from the analyses. There were significant correlations between the activity of 210 Pbex and organic C under both forest and scrub, but the strongest were in the surface layers of soil under forest. More than 80% of the total activity of 210 Pbex was adsorbed in the upper 6 cm, with an exponential decline with increasing depth. The decline was modelled with exponential functions fitted by non‐linear least‐squares regression to predict the depth distributions of 210 Pbex and organic C in forest and scrub soils separately. The results confirm the viability of the use of 210 Pbex in stony soil as an indicator of soil redistribution and show the significant effect of vegetative cover. These results provide useful information about sampling design for future research if the radionuclide 210 Pbex is used for assessing soil redistribution in similar Mediterranean environments. Highlights: Characterizing the vertical distribution of 210 Pbex requires high resolution sampling (2 cm). In uncultivated soil of the Pre‐Pyrenees the fallout, 210 Pbex, is retained in the uppermost 14 cm. The distribution of 210 Pbex matches that of the organic matter down the profile. Vegetation affects the surface activity of 210 Pbex in the soil, being greater under forest than under scrub.